Psikologi Kepribadian dalam Pendidikan Tinggi di Kampus - Burahnudin Burahnudin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
Personality psychology in the context of higher education on campus is the scientific study of a person's nature or character, especially the character and characteristics of students. The main goal of studying personality psychology in education is to help educators understand the unique characteristics of each student, optimize the learning process, build better relationships and address educational challenges. In a broader sense, personality psychology in education is not only limited to understanding individual traits, but also involves the application of scientific methods to understand how knowledge, understanding and behavior can be developed effectively which includes the use of psychological methods, the development of learning strategies student-centered and improving the quality of education. Personality psychology plays a vital role in higher education by providing the insights necessary to understand students in depth. With this knowledge, educators can optimize their teaching methods to create more effective, personalized, and meaningful learning experiences. Thus, personality psychology helps create an educational environment that supports maximum academic and personal development.